Particles and the universe proceedings of the twelfth Lake Louise Winter Institute : Lake Louise, Alberta, Canada, 16-22 February 1997 (World Scientific Publishing Co. Pte Ltd., 1998)
Includes results from LEP2, primordial nucleosynthesis and dark matter, experiments to measure the cosmic background radiation and experiments in the laboratory with radioactive beams to ascertain the importance of astrophysics in the universe